Societal Agents in Law A Macrosociological Approach - Barnett, Larry D. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In this two-volume set, Larry D. Barnett delves into the macrosociological sources of law concerned with society-important social activities in a structurally complex, democratically governed nation. Barnett explores why, when, and where particular proscriptions and prescriptions of law on key social activities arise, persist, and change. The first volume, Societal Agents in Law: A Macrosociological Approach, puts relevant doctrines of law into a macrosociological framework, uses the findings of quantitative research to formulate theorems that identify the impact of several society-level agents on doctrines of law, and takes the reader through a number of case analyses. The second volume, Societal Agents in Law: Quantitative Research, reports original multivariate statistical studies of sociological determinants of law on specific types of key social activities. Taken together, the two volumes offer an alternative to the almost-total monopoly of theoryand descriptive scholarship in the macrosociology of law, comparative law, and history of law, and underscore the value of a mixed empirical/theoretical approach.